Geçmişten Günümüze Batı Müziği Tarihine Yolculuk - Aslan, Uğur; Hongur, Gönenç; Durmuş, Sadık Uğraş; Ergene, Emrah; Karabiber, Onur; Yalınkılıç, Erdinç; Yavuz, Elif Damla; Önder, Erdener; Sakarya, Uğur Cihat; Keleş, Ali (2024)
-